6 UMP subjects listed in QSWUR by Subject 2022, world-recognised - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PEKAN, 6 April 2022 - Six Universiti Malaysia Pahang (UMP) subjects are ranked among the world’s best based on the recently announced QS World University Rankings (QSWUR) by Subject 2022 rating.